2019
DOI: 10.1016/j.jcte.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and malignancy rates classified by The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) – An 8-year tertiary center experience in Thailand

Abstract: Incidence and Malignancy Rates Classified by The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) – An 8-year Tertiary Center experience in Thailand. Background Fine-needle aspiration (FNA) of the thyroid is considered the best diagnostic tool for preoperative evaluation of thyroid nodules. The introduction of T he B ethesda S ystem for R eporting T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 25 publications
14
18
3
Order By: Relevance
“…[19][20][21] Additionally, in this study, over half of thyroid nodules were classified in category I (undiagnosed) and II (benign) and the BRAF V600E mutation rates were 12% and 4%, respectively, with similar malignancy rates reported in previous studies. 21 in line with the fact that PTCs are most likely to occur in young women. 5 In the UK, it has been reported that the incidence rates of thyroid cancer in women reach a peak at ages 35-39 years and then decline steadily.…”
Section: Discussionsupporting
confidence: 82%
“…[19][20][21] Additionally, in this study, over half of thyroid nodules were classified in category I (undiagnosed) and II (benign) and the BRAF V600E mutation rates were 12% and 4%, respectively, with similar malignancy rates reported in previous studies. 21 in line with the fact that PTCs are most likely to occur in young women. 5 In the UK, it has been reported that the incidence rates of thyroid cancer in women reach a peak at ages 35-39 years and then decline steadily.…”
Section: Discussionsupporting
confidence: 82%
“…A 3 month waiting period prior to any repeat FNAC does not improve the diagnostic yield or alter patient care algorithm. 15,40 Malignancy and surgical procedure rates were found to be similar among patients who did or did not have a re-FNAC. 41 On the basis of these collective results, the question arises why the malignant tumors, that is, PTCs were missed on initial FNA.…”
Section: Discussionmentioning
confidence: 85%
“…As a result of these revised items, RoM of AUS/FLUS (including NIFTP) increased from 5%-15% to 10%-30% but remain relatively unchanged (6%-18%) if excluding NIFTP as a diagnosis of benign/nonmalignant thyroid condition. 15 The NIFTP concept was accepted and included into the latest version of the WHO classification of tumors of endocrine organs and the revised version of TBSRTC also took into account its presence, but did not create a specific diagnostic category for it, as NIFTP diagnosis is not possible on FNAC. 16 If cytopathology demonstrated AUS, clinical recommendations are for repeat FNAC evaluation under ultrasound (US) guidance, or lobectomy (especially if the nodule is large or if it has high-risk sonographic features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bethesda classification system gives six categories for thyroid lesions in order of increasing rate of malignancy. 1 Indeterminate lesion which are not clearly benign or malignant has been a walk on the fence for both clinicians and pathologist. Hence, the category III which is labelled as "Atypia of undetermined significance" / "follicular lesion of undetermined significance" is for separating lesions with insufficient degree of atypia to qualify for any of the suspicious categories.…”
Section: Introductionmentioning
confidence: 99%